Merging Tenets of Relational Cultural Theory, Feminism, and Wonder Woman for Counseling Practice. Issue 3 (3rd July 2021) - Hammer, Tonya R.; Chan, Christian D.; Kavanaugh, Katherine E.; Hadwiger, Ashley N.
ABSTRACT: The most recent release of the film "Wonder Woman" signified a pivotal moment to highlight societal forces of oppression along with distinct launching points to advocate for women. Relational-cultural theory (RCT) is a feminist framework used in counseling and supervision that acknowledges the resilience and empowerment found in authenticity, mutuality, and growth-fostering relationships. Researchers have documented the widespread integration and proliferation of RCT due to its intuitive coherence with professional counseling and advocacy. The film "Wonder Woman" serves as a modern and entertaining platform that illustrates how early connection, societal representations, and growth-fostering relationships can serve as a source of empowerment and advocacy for women, despite superhero powers. Combined with an elaboration of relational-cultural theory (RCT) as the underlying framework, this article addresses three overarching areas: (a) synopsis of "Wonder Woman" and its implications for feminism, women, and advocacy; (b) core tenets of RCT; and (c) practical aspects of using "Wonder Woman" in counselor education, supervision, and counseling practice.